EFEKTIVITAS PROGRAM SQ3R TERHADAP KEMAMPUAN PEMAHAMAN MEMBACA SISWA KELAS VI SEKOLAH DASAR - Arthur Huwae; Putri Pratiwi Lessy; Dhenisa Titis Eksa Putri; Ruby Bulan Prabandari; Ruly Feby Kurniasari; Anugrah Imam Sarwono; Yemima Joy Christina; Darrel Samuel Maukar; Yemima Claudya Br Sembiring; Shella Monica Santoso; Bencarel Reinhard Soputan Vici; Rizky Chandra (Fakultas Psikologi Universitas Kristen Satya Wacana, 2025)
The inability to read is one of the major problems frequently encountered in elementary school education, particularly among upper-grade students. This condition can have significant consequences when students continue their education to the next level. One approach considered effective in improving reading ability is the application of the SQ3R strategy. This study aims to enhance the reading comprehension of sixth-grade students at SDN Kutowinangun 8 Salatiga through SQ3R training methods. The research employed a quantitative experimental approach using a one-group pretest–posttest design. A total of 35 sixth-grade students participated in this study. The instruments used included an SQ3R training module as well as pretest and posttest sheets to measure improvements in students’ reading comprehension. Data were analyzed using the Wilcoxon Signed Rank Test. The results indicate that SQ3R training is effective in improving the reading comprehension of sixth-grade students at SDN Kutowinangun 8 Salatiga. These findings suggest that reading comprehension is a crucial skill for sixth-grade students at SDN Kutowinangun 8 Salatiga, as it helps them adapt to subsequent levels of education.